Evaluasi Kurikulum 2013 Pembelajaran IPS Di Sekolah Menengah Pertama: Tantangan Dan Peluang (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The implementation of the program in 2013 has brought changes to the learning process. Minister of Education and Culture Regulation no. Decree Number 65 of 2013 concerning Primary and Secondary Education Process Standards points to the need for learning processes to be guided by the principles of a scientific approach. The scientific approach applies to all subjects at all levels. Adopting a scientific approach can certainly cause its own difficulties, especially in exact subjects such as social studies. This research aims to conduct a study of the implementation of the 2013 social studies curriculum in secondary schools that implement the 2013 curriculum. The results of this research show that in general the implementation of the 2013 social studies curriculum in secondary schools uses the mutually adaptive curriculum implementation method, social studies teachers still encounter several obstacles, doubts doubtful and difficult to adapt to real conditions. This is proven by the academic performance of social studies teachers who use scientific methods, but most social studies learning is only carried out in the classroom so it does not provide special training learning experiences for students.